2019
DOI: 10.3389/fonc.2019.01261
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0007841: A Novel Potential Biomarker and Drug Resistance for Multiple Myeloma

Abstract: Purpose: Circular RNA (circRNA) is a key regulatory factor in the development and progression of human tumors. However, the working mechanism and clinical significance of most circRNAs remain unknown in human cancers, including multiple myeloma (MM).Patients and Methods: This study employs high-throughput circRNA microarray with bioinformatics to identify differentially expressed circRNAs in patients with MM. The hsa_circ_0007841 expressions were observed in the MM tissues of 86 patients. Drug-resistant cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…Further studies suggested that circ_0007841 promoted the proliferation, cell cycle, metastasis and inhibited the apoptosis of MM cells. These findings demonstrated that circ_0007841 might be an important biomarker for MM patients, which was in agreement with the former article [28]. However, the regulatory mechanism by which circ_0007841 promoted the progression of MM was unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Further studies suggested that circ_0007841 promoted the proliferation, cell cycle, metastasis and inhibited the apoptosis of MM cells. These findings demonstrated that circ_0007841 might be an important biomarker for MM patients, which was in agreement with the former article [28]. However, the regulatory mechanism by which circ_0007841 promoted the progression of MM was unclear.…”
Section: Discussionsupporting
confidence: 91%
“…11 CircRNAs may also play a key role in the development of drug resistance. Recently, multiple studies have highlighted the key roles of ncRNAs in chemoresistance of cancer, such as HCC, 142,249 lung cancer, 250,251 gastric cancer, 252,253 breast cancer, 254,255 multiple myeloma, 256 acute myeloid leukemia, 234 prostate cancer, 257 bladder cancer, 258 among others. The up-to-date information regarding the role of circRNAs in the resistance of tumors to chemotherapy has been recently summarized with multiple mechanisms, such as modulating various regulatory pathways and processes including the ceRNA regulatory network axis, EMT process, regulation of ABC transporters, apoptosis, autophagy, and CSCs, among others although many physiological processes and biological signaling pathways through which circRNAs are involved in drug resistance still remained unknown.…”
Section: Discussion and Prospectivementioning
confidence: 99%
“…Hsa_circ_0007841 is upregulated in bortezomib-resistant multiple myeloma (MM) cells and significantly correlated with the poor prognosis of MM patients [150]. CiRS-7 is downregulated in melanoma and negatively correlates with melanoma progression by interacting with the RBP IGF2BP3.…”
Section: Miscellaneous: Myeloma and Melanomamentioning
confidence: 99%